“Dress like the Global North and eat like the Global South”: why do faculty contributions to university research productivity matter? - Marasigan, Arlyne C.; Hajan, Bonjovi; Castulo, Nilo Jayoma; Obliopas, Riomar; Digo, Gerry S.; Imam, Ombra A.; De Vera, Jayson L.; Aquino, John Michael; Anito, Jovito C.; Colicol, Fernigil; Buenaventura, Ma Laarni; Koirala, Ishwar; et al. (Frontiers in Education, 2025)
The long-standing disparity in research standards between Global South and Global North universities places immense pressure on higher education, affecting faculty research productivity and global competitiveness. This policy brief argues that aligning with the Global North standards to achieve international competitiveness and sustainability requires strategic policy interventions that address both human and financial constraints. Based on the evidence, the University of the Philippines, Polytechnic University of the Philippines, and Mindanao State University are the top three state-funded universities with the highest number of faculty members. Additionally, the University of the Philippines receives the highest research funding allocation and has produced over a thousand Scopus-indexed publications between 2020 and 2024, compared to other universities with fewer than 200 publications. The top ten challenges faced by Filipino faculty members in conducting research based on 58 respondents in a survey include time constraints, financial limitations, being overburdened with work, limited research exposure, coordination difficulties, lack of research training, family commitments, poor writing skills, lack of motivation, technical guidance, and publication pressure. Thus, this policy brief recommends that higher education institutions strengthen research governance and compliance, bridge research disparities for global competitiveness, and recalibrate research standards for sustainable growth. These policy recommendations not only blur research polarization but also advance knowledge sharing and data sharing to foster a sustainable research culture and faculty productivity, positioning the country as a key player in the global academic community.